The formation and development of academic terminology (Herald of Journalism, 2020)
This article is devoted to the academic terms of higher education of the Republic of Kazakhstan.The purpose of the given article is to show the formation and development of academic terminology based  on the terms in the official documents of two universities of Kazakhstan. The academic terms were re- trieved from the Academic Policy, Academic Calendar, Academic Transcript, Individual Education Plan  of Al-Farabi Kazakh National University and Satbayev Kazakh National Technical Research University. The academic terminology of higher education is constantly in change due to the circumstances sur- rounding the development of human life. The formation of terms used in a certain sphere of human activities reflects the development of the society. The value of this study is that the academic terms in this article are divided into academic terminology of Latin origin, i.e. academic terms, which have Latin roots, academic terminology of the period before joining the Bologna process, and academic terminol- ogy of the Bologna process. The scientific and practical significance of the study is that the processes   of globalization, the Bologna process, exchange programmes, etc. are leading to the formation of single space in education system of not only Kazakhstan, but other countries as well. The practical significance of the work results is that the research of this topic is helpful for students and professors, who participate in exchange and academic mobility programmes. There has been little research on this particular topic and the research in this article triggers deeper investigation with more valuable results in linguistics and lexicography in the future
Keywords: terminology,academic terminology, Bologna process, formation, development, aca- demic mobility.